BULLYING AND VERBAL-NONVERBAL COMMUNICATION AMONG A GROUP OF COLLEGE STUDENTS - Siti Khadijah (Avant Garde, 2018)
Bullying is one of problems of Universities in Indonesia. In 2006, there were 29 cases of physical violence, 67 cases of sexual violence , and 96 ases of psychic violence in college. This research aimed to analyse bullying cases among a group of college students from the point of views of verbal and non-verbal communications. Using qualitative method, there were acts of bullying in the form of verbal communication experienced by victims in the form of harsh words that belittle the victim, scolding, screaming, giving negative nickname even a month-monthly friend of a class, and done in front of the crowd. While harassment in the form of nonverbal communication is a cynical view of the perpetrator against the victim, the view of degrading the victim by considering the victim as a "fool", making the distance with the victim by not including victims in the chat group, not invited to take a walk, be kept in class. In addition, the victim also got a kick, spit on, thrown with goods. Negative impacts are anxiety, quarreling with abusers, and declining learning achievement